A Case Study of Municipal Taxation by Citation - Carpenter, Dick M. (Criminal justice policy review, 2022)
This study examines taxation by citation—local governments using code enforcement and the justice system to raise revenue rather than solely to advance public health and safety. It does so through a detailed case study of Morrow, Riverdale, and Clarkston, three Georgia cities with a history of prolific revenue generation through fines and fees from traffic and other ordinance enforcement. Results suggest taxation by citation is a function of the perceived need for revenue and the ability to realize it through code enforcement. Moreover, the phenomenon may be a matter of systemic incentives. City leaders need not be motivated by simple rapaciousness. They may see fines and fees revenue as the answer to their cities’ problems. Once in effect, the mechanisms necessary for taxation by citation—such as highly efficient court procedures—may stick, becoming business as usual.